1995
DOI: 10.1002/jmv.1890450318
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination in infants of mothers infected with human immunodeficiency virus

Abstract: A study was conducted to investigate the immunogenicity of a recombinant DNA hepatitis B vaccine in neonates and children of HIV-infected women. Immunization against hepatitis B consisted of three 10 micrograms doses of the vaccine administered on a 0-, 1- and 6-month schedule. The children were followed up for an average of 11 months. Of the 118 HIV-positive neonates who participated in the study, 95 lost their HIV antibodies during the follow-up period. Most (94.2%) of the latter who completed the study resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In children with perinatally acquired infection, response rates range from 20 – 78% 16. Correlation of response with CD4+ T-cell (CD4) counts or percentages, HIV-related symptoms, and younger age are reported but with inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…In children with perinatally acquired infection, response rates range from 20 – 78% 16. Correlation of response with CD4+ T-cell (CD4) counts or percentages, HIV-related symptoms, and younger age are reported but with inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…[1116] Risk factors for lack of a vaccine response include higher HIV RNA at the time of vaccination,[17, 18] anti-hepatitis C virus (HCV) positivity,[19, 20] and lower nadir CD4 cell count prior to vaccination,[21, 22] while CD4 cell count at the time of vaccination has not been consistently predictive. [11, 13, 15–18, 20, 23, 24] Several studies have also documented reduced durability of serologic responses to HBV vaccine in those infected with HIV compared to HIV-negative individuals[12, 23, 25, 26] leading some to recommend booster doses for HIV-infected patients when antibody to HBV surface antigen (HBsAb) levels fall below 10 IU/L,[2] although data supporting this practice are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Standard immunization schedules with a three‐dose regimen confer protection [antibodies to HBsAg (anti‐HBs) ≥10 mUI/mL] in >95% of immunocompetent children [8] but in HIV‐1‐infected patients the same regimen has been associated with lower seroconversion rates (25–41% in children) [9,10]. Some investigators have suggested that an increase in the dose or the frequency may improve the response in immunodeficient children [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also produced conflicting results on the role of CD4 cell counts as predictors of HBV vaccine response in HIV‐infected adults [13] and children [9,10,14,15]. No study has to our knowledge evaluated the response rate to HBV vaccination in HIV‐infected children receiving highly active antiretroviral therapy (HAART).…”
Section: Introductionmentioning
confidence: 99%